We have to solve

x + y = 5 ...(1)

x^2 + y^2 = 13 ...(2)

From (1) x = 5 - y

Substituting in (2)

(5 - y)^2 + y^2 = 13

=> 25 + y^2 - 10y + y^2 = 13

=> 2y^2 - 10y + 12 = 0

=> y^2 - 5y + 6 = 0

=> y^2 - 3y - 2y + 6 = 0

=> y(y - 3) - 2(y - 3) = 0

=> (y - 2)(y - 3) = 0

=> y = 2 and y = 3

x = 3 and 2

**The solutions of the equations are (2, 3) and (3,2)**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now